Additional chromosomal abnormalities in Philadelphia positive chronic myeloid leukemia - Tashfeen, Sunila (Pak J Med Sci, 2020)
OBJECTIVE: To determine the frequency of additional chromosomal abnormalities in Philadelphia chromosome positive Chronic Myeloid Leukemia (CML) by conventional cytogenetic analysis. METHODS: This descriptive cross sectional study was conducted at Armed Forces Institute of Pathology (AFIP), Rawalpindi, from January 2012 to December 2016. A total number of 528 newly diagnosed CML patients were included in the study. The subjects were tested for the presence of Philadelphia (Ph) chromosome and other additional cytogenetic abnormalities by conventional cytogenetic analysis interpreted according to International System of Human Cytogenetic Nomenclature (ISCN) criteria. Molecular analysis for BCR-ABL was also performed for each patient. The additional cytogenetic abnormalities were then classified into major route abnormalities and minor route abnormalities. RESULTS: Out of the 528 newly diagnosed CML patients, 378 (71.6%) were males and 150 (28.4%) were females. The age of patients ranged between 18 to 74 years. Four hundred and ninety-eight (94.3%) patients showed Philadelphia chromosome on karyotyping while 30 (5.7%) were negative for the Philadelphia chromosome. On analysis of these 498 Philadelphia positive patients, additional cytogenetic aberrations were detected in 26 (4.9%) patients. Of these, 7 (1.3%) had major route abnormalities while 19 (3.6%) had minor route abnormalities. CONCLUSION: The frequency of additional chromosomal abnormalities in our study were not in accordance with previous local and international studies.